CXCR4 engagement triggers CD47 internalization and antitumor immunization in a mouse model of mesothelioma. Issue 6 (6th May 2021) - Mezzapelle, Rosanna; De Marchis, Francesco; Passera, Chiara; Leo, Manuela; Brambilla, Francesca; Colombo, Federica; Casalgrandi, Maura; Preti, Alessandro; Zambrano, Samuel; Castellani, Patrizia; Ertassi, Riccardo; Silingardi, Marco; et al.
Abstract: Boosting antitumor immunity has emerged as a powerful strategy in cancer treatment. While releasing T‐cell brakes has received most attention, tumor recognition by T cells is a pre‐requisite. Radiotherapy and certain cytotoxic drugs induce the release of damage‐associated molecular patterns, which promote tumor antigen cross‐presentation and T‐cell priming. Antibodies against the "do not eat me" signal CD47 cause macrophage phagocytosis of live tumor cells and drive the emergence of antitumor T cells. Here we show that CXCR4 activation, so far associated only with tumor progression and metastasis, also flags tumor cells to immune recognition. Both CXCL12, the natural CXCR4 ligand, and BoxA, a fragment of HMGB1, promote the release of DAMPs and the internalization of CD47, leading to protective antitumor immunity. We designate as Immunogenic Surrender the process by which CXCR4 turns in tumor cells to macrophages, thereby subjecting a rapidly growing tissue to immunological scrutiny. Importantly, while CXCL12 promotes tumor cell proliferation, BoxA reduces it, and might be exploited for the treatment of malignant mesothelioma and a variety of other tumors. Synopsis: Induction of antitumor immunity is a successful strategy in cancer treatment. This study reports that BoxA, a fragment of the alarmin HMGB1, induces tumor remission and antitumor immunity in mouse models of mesothelioma and colon carcinoma. Both BoxA and the chemokine CXCL12 bind the G‐Protein Coupled Receptor CXCR4. CXCR4 and CD47 are in contact on the surface of tumor cells and co‐internalize upon CXCR4 engagement by either BoxA or CXCL12. Both CXCL12 and BoxA induce the phagocytosis of tumor cells by macrophages. BoxA inhibits tumor cell growth and induces antitumor immunological memory in syngeneic mouse models of mesothelioma or colon carcinoma. CXCL12 is suggested to mediate a similar response (Immunogenic Surrender) in a fraction of untreated tumor‐bearing mice. Abstract : Induction of antitumor immunity is a successful strategy in cancer treatment. This study reports that BoxA, a fragment of the alarmin HMGB1, induces tumor remission and antitumor immunity in mouse models of mesothelioma and colon carcinoma.